Selittävätkö koettu stressi ja itsearvioitu stressinhallintakyky sosioekonomisen aseman ja masennusoireiden välistä yhteyttä iäkkäillä henkilöillä? - Kyttälä, Sini (2024)
Socioeconomic health inequalities are substantial in Finland. The health of people with lower socioeconomic status is worse in many ways and depressive symptoms are more common among them. Although the health of the population has improved in general, health inequalities have persisted. The aim of this study was to investigate the association between socioeconomic status and depressive symptoms, and to find out if the perceived stress and self-rated stress-coping ability explain the association between them in older adults.